Pengaruh Teknik Kekaguman Berbantuan Media Audio Visual dalam Pembelajaran Menulis Teks Puisi - Shalihah, Mar’atus; Sakaria, Sakaria (Nuances of Indonesian Language, 2023)
This study aims to determine the effect of the awe technique assisted by audio-visual media on students learning to write poetry texts in class VIII SMP Negeri 27 Makassar. The data for this research is quantitative data from students' pretest and posttest results. The type of research used by researchers in this study is quantitative using a pre-experimental design, namely a one-group pretest and posttest design. The population in this study was class VIII students of SMP Negeri 27 Makassar, with a total of 358 students divided into 11 classes. The sampling technique used in this study was purposive sampling. The sample taken in this study was from class VIII 9 which totaled 35 students. The data analysis technique used in this research is quantitative descriptive data analysis. The results showed that the average value of students' short story writing in the pretest was 60.9 while the average value in the pretest was 83. If the result of one sample test shows the value of tcount > ttable, which is 8.398 > 2.032 then the hypothesis H0 is rejected and H1 is accepted. This study shows that the use of awe techniques assisted by audiovisual media has an effect on learning to write poetry texts.